'What meaning does somebody's death have, what meaning does somebody's life have?' Psychotherapists' stories of their work with suicidal clients. Issue 5 (19th October 2016) - Nicholl, Elizabeth; Loewenthal, Del; Gaitanidis, Anastasios
ABSTRACT: Working with suicidal clients is perceived to be demanding and anxiety provoking for psychotherapists. This investigation explores what it is like for psychotherapists who work with suicidal clients, particularly as within the prevailing culture there is an increasing focus on strategies aimed at suicide prevention. Five themes were identified through narrative analysis, with support systems such as supervision and peer support being seen as vital in surviving working with suicidal clients. However, there is also ambivalence about involving other professionals, such as mental health services, as there is a sense that to do so may be anti-therapeutic and unhelpful to the client. Overall, what emerges from this study is that it is important to challenge the prevailing culture in which a medical discourse is dominant, in order to find a different way of talking about suicide and despair.